Implementation of temporary bike lanes as support tools for mobility in Bogotá, Colombia, during the COVID-19 emergency - Olmos, Camilo Andrés Mora; Borchers, Tatiane; Guerreiro, Thais de Cassia Martinelli (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
The COVID-19 pandemic presents itself as the greatest health challenge of the 21st century. Among the key measures to contain the spread of SARS-CoV-2 is social isolation, which has affected the processes related to urban mobility. With the need to reduce passengers on public transport and to curb an increase in car trips, several cities have sought to encourage the use of bicycles. This study analyzes the implementation of temporary bike lanes in Bogotá, Colombia, as a measure to confront the COVID-19 pandemic, the changes derived from this measure, and carries out a perception survey on the implementation of this infrastructure. The results show the implementation of 74 kilometers of temporary bike lanes, of which some of them have already been transformed into permanent; the survey shows an increase in the modal participation of the bicycle and that there is an acceptance of the transformation of the infrastructure from temporary to permanent character. However, participants evaluated safety and infrastructure quality criteria negatively. The city’s solutions, although capable of improvement, contribute to other cities implementing cycling infrastructure in the pandemic scenario and work to ensure a modal transition in the post-pandemic period.